Taxidermy as Knowledge: Review of Rachel Poliquin, The Breathless Zoo: Taxidermy and the Cultures of Longing - Walls, Alissa (Humanimalia, 2013)
Rachel Poliquin, The Breathless Zoo: Taxidermy and the Cultures of Longing. University Park: Pennsylvania State University Press, 2012. 272 pp. 34.95 hb. 29.95 pb.